Physcion Protects Against Ethanol-Induced Liver Injury by Reprogramming of Circadian Clock - Yao, Youli; Zuo, Along; Deng, Qiyu; Liu, Shikang; Zhan, Tianying; Wang, Maolin; Xu, Haidong; Ma, Junxian; Zhao, Yingying (Frontiers in Pharmacology, 2020)
The circadian clock plays a key role in our daily physiology and metabolism. Alcohol consumption disrupts the circadian rhythm of metabolic genes in the liver; however, the potential contribution of circadian clock modulation to alcoholic liver disease (ALD) is unknown. We identified a novel liver protective agent, physcion, which can alleviate fat accumulation and inflammation in ALD mice via reprogramming the hepatic circadian clock. The model of alcoholic hepatitis was established by intragastrically administering ethanol. In vitro, physcion was investigated by treating HepG2 cells with ethanol. The role of circadian clock in Physcion caused liver protection was tested by knocking down the core circadian gene Bmal1. Physcion application caused reduced lipogenesis and alleviated inflammation in alcohol-induced mice. In alcoholic hepatosteatosis models, physcion upregulated the core circadian genes. And the circadian misalignment triggered by ethanol was efficiently reversed by physcion. Physcion attenuated lipogenesis via reprogramming the circadian clock in HepG2 cells. Suppression of Bmal1 by RNA interference abolished the protective of physcion. In addition, Physcion binds to the active pocket of BMAL1 and promotes its expression. The study identified the novel liver protective effects of physcion on alcohol-induced liver injury, and modulation of the core circadian clock regulators contributes to ALD alleviation. More importantly, strategies targeting the circadian machinery, for example, Bmal1, may prove to be beneficial treatment options for this condition.